The great book of animals: The comprehensive illustrated guide to 750 species and their environments (Philadelphia, Pennsylvania, 1997)
This book identifies and explores every major animal group from the smallest single-celled protozoans to the largest primates. Clear, informative descriptions and hundreds of full-color illustrations bring us directly into the domain of invertebrates, fish, amphibians, retiples, birds, and mammals
Keywords: animals,birds,zoology